Differential influences of LDL cholesterol on functional outcomes after intravenous thrombolysis according to prestroke statin use - You-Ri Kang; Joon-Tae Kim; Ji Sung Lee; Beom Joon Kim; Kyusik Kang; Soo Joo Lee; Jae Guk Kim; Jae-Kwan Cha; Dae-Hyun Kim; Tai Hwan Park; Kyung Bok Lee; Jun Lee; et al. (Scientific Reports, 2022)
Abstract This study aimed to elucidate whether low-density lipoprotein cholesterol (LDL-C) levels differentially affect functional outcomes after intravenous thrombolysis (IVT) depending on prestroke statin use. Patients with acute ischemic stroke treated with IVT were categorized into low, intermediate, and high LDL-C groups based on LDL-C levels at admission (< 100/100–130/ > 130 mg/dl, respectively). Multivariable logistic regression analyses were performed to explore the relationships between LDL-C and clinical outcomes (good outcomes at 3 months, modified Rankin Scale scores 0–2). The interaction between LDL-C levels and prestroke statin use regarding functional outcomes was investigated. Among the 4711 patients (age, 67 ± 12 years; males, 62.1%) who met the eligibility criteria, compared with the high LDL-C group, the low and intermediate LDL-C groups were not associated with good outcomes at 3 months according to the multivariable analysis. A potential interaction between the LDL-C group and prestroke statin use on good outcomes at 3 months was observed (P interaction = 0.07). Among patients with prestroke statin use, low (aOR 1.84 [1.04–3.26]) and intermediate (aOR 2.31 [1.20–4.47]) LDL-C groups were independently associated with a greater likelihood of having a 3-month good outcome. Our study showed that LDL-C was not associated with a 3-month good outcome, but prestroke statin use could modify the influence of LDL-C levels on functional outcomes after IVT.